2011
DOI: 10.1166/jnn.2011.5292
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Mn2+ Doping on the Luminescence Properties of 12CaO·7Al2O3:Eu2+ Nanocrystal Phosphor

et al.

Abstract: The long lasting blue phosphorescence (LLP) and photostimulated luminescence (PSL) after ultraviolet light irradiation at room temperature in 12CaO 7Al2O3:xEu2+, yMn2+ (x = 0, 0.001; y = 0, 0.01) prepared by the chemical co-precipitation method were observed. It was shown that novel oxide 12CaO 7Al2O3:Eu2+, Mn2+ (C12A7:Eu2+, Mn2+) with unique nanocage structure can store energy when irradiated with 365 nm photons. And photon energy can be subsequently released by exposed to 980 nm light. The codopant Mn2+ enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…suggested that C12A7 derivatives with empty cages could be used as electro‐active materials. Yan et al . synthesized rare earth and transition metals co‐doped C12A7–Eu 2+ /Mn 2+ .…”
Section: Derivatives Of C12a7mentioning
confidence: 99%
See 1 more Smart Citation
“…suggested that C12A7 derivatives with empty cages could be used as electro‐active materials. Yan et al . synthesized rare earth and transition metals co‐doped C12A7–Eu 2+ /Mn 2+ .…”
Section: Derivatives Of C12a7mentioning
confidence: 99%
“…Matsuishi et al 52 suggested that C12A7 derivatives with empty cages could be used as electro-active materials. Yan et al 118 synthesized rare earth and transition metals co-doped C12A7-Eu 2+ / Mn 2+ . These co-doped derivatives showed long-lasting blue phosphorescence (LLP) and photo-stimulated luminescence (PSL) after ultraviolet light irradiation at room temperature.…”
Section: Derivatives Of C12a7mentioning
confidence: 99%
“…Besides nanoparticles, -tubes, -wires, -rods, -needles, and -sheets and thin films, Eu 2+ -based nanophosphors have been also synthesized with alternative shapes such as nanosized cuboids, , truncated octahedron, cones, and cages . The main objective of the work of Lu et al, for instance, is to explore different shapes of Eu 2+ -doped barium silicate nanostructures with general formula Ba 3 Si 5 O 13 by means of the hydrothermal method, applying ethylenediamine as a shape-directing agent.…”
Section: Exceptional Morphologies Of Eu2+ Nanophosphorsmentioning
confidence: 99%
“…Photoluminescence spectra have not only a broad emission band centered at 445 nm originating from the 4f 6 5d 1 to 4f 7 transitions of Eu 2+ but also red emission peaks originating from Eu 3+ ions . In addition, nanocones of CaAl 2 O 4 :Eu 2+ with a 2–20 μm length, 200–1000 nm diameter in one end, and 40–200 nm diameter in the other end were produced with the aid of a thermal evaporation-based technique, and, moreover, 12CaO·7Al 2 O 3 : x Eu 2+ ,Mn 2+ was synthesized by the coprecipitation method, forming a nanocage structure for storing applications …”
Section: Exceptional Morphologies Of Eu2+ Nanophosphorsmentioning
confidence: 99%
See 1 more Smart Citation